2016
DOI: 10.4103/2321-0656.176572
|View full text |Cite
|
Sign up to set email alerts
|

Self-care practices among diabetes patients registered in a chronic disease clinic in Puducherry, South India

Abstract: Background: In management of diabetes, self-care plays an important role in prevention of complications. This study aims to find the proportion of diabetic patients following the recommended self-care practices in an urban area of Puducherry. Materials and Methods: Consecutive eligible patients registered in chronic disease clinic were interviewed using Summary of Diabetes Self Care Activities Score (SDSCA) questionnaire. Self-care practices were evaluated in domains of diet, physical activity, foot-care, adhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
34
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 8 publications
5
34
2
Order By: Relevance
“…showed that the prevalence of diabetic medication adherence was 95%, which was significantly higher compared to our study. [ 24 ] The regional and rural-urban differences could have been the reason for this difference.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…showed that the prevalence of diabetic medication adherence was 95%, which was significantly higher compared to our study. [ 24 ] The regional and rural-urban differences could have been the reason for this difference.…”
Section: Discussionmentioning
confidence: 99%
“…75.2% of the study population had satisfactory blood sugar monitoring which is similar to the results reported by Selvaraj et al . [ 24 ] and study done in Mangalore. [ 20 ]…”
Section: Discussionmentioning
confidence: 99%
“…However Selvaraj et al in Puducherry had found high level of medication adherence as 95.6% patients had taken recommended medication for at least 6 days in a week, which might be ascribed to facility based study setting. 17 Blood glucose monitoring is now becoming more adhered to due to availability of home available monitoring devices. Self-testing for recommended number of times was done by 20.2% in present study, which is consistent with study in Gujarat.…”
Section: Discussionmentioning
confidence: 99%
“…[ 9 12 ] Recent studies from India showed compliance levels of 8% to 45% in checking feet. [ 11 13 14 ] At the end of the intervention, an additional improvement of 1.95 days/week in SDSCA mean score and 33.5% increase in compliance for checking of feet was observed in intervention group compared to control group. This concurs with previous studies from Pondicherry (increase of 2.1 days/week)[ 15 ] and Iran (improvement of 2.9 days/week).…”
Section: Discussionmentioning
confidence: 99%